Physician perspectives on reducing harm and supporting emergency department patients who use drugs. - Zoe K D Collins; Elaine Hyshka; Karine J Lavergne; Savannah M Weber; Ginetta Salvalaggio; Cindy Jiaxin Xue; Arlanna Pugh; Janusz Kaczorowski; Aaron M Orkin; Andrew Kestler; Kathryn A Dong (PLoS ONE)
Background People who use drugs (PWUD) frequently seek care in the emergency department (ED). Little is known about ED physician perspectives and experiences integrating a harm reduction approach into care, including interventions that reduce the health, social and legal consequences of drug use without requiring a reduction in drug use. Objective This study aimed to describe the experiences of Canadian emergency physicians caring for PWUD, and facilitators and barriers to implementing harm reduction interventions in the ED. Methods Purposive sampling, using an existing national network, and snowball sampling techniques were used to recruit practicing emergency physicians. Semi-structured, one-on-one telephone interviews were conducted until theoretical data saturation was achieved. Interview recordings were transcribed and analyzed using latent content analysis. Interviews took place between June 2019 and February 2020. This work is a secondary analysis specifically focused on harm reduction approaches to care. Results 32 physician interviews were included. Participants had a median of 10 years of experience (range 1-33) and most (29/32) worked in urban EDs. Participants highlighted the complexities of caring for PWUD, including the intersection of structural vulnerability with substance use. The ED environment varied across Canada and either facilitated or hindered the adoption of harm reduction interventions. Additional barriers included a lack of training and experience; lack of community follow-up care; insufficient ED funding and staffing resources; and, tensions over the appropriate scope of emergency medicine practice. Facilitators included tailored education and training; specialized multidisciplinary teams; ED harm reduction champions; and standardized protocols. Conclusions Though variability existed in the adoption and practice of harm reduction in Canadian EDs, most interviewed physicians supported a harm reduction approach to care. To facilitate widespread ED adoption of harm reduction interventions, there is a need for standardized guidance, supplemental resources, facilitated culture change, and sufficient community-based services.